AB0744 A "lost-to-follow-up" autoantibody for the diagnosis of autoimmune disease: prevalence and clinical characteristics of anti-nor90/hubf positive patients. (12th June 2018) - Koutsianas, C.; Levasseur, K.; Rutter, M.; Webber, C.; Bhole, M.; Bell, C.; Douglas, K.
Abstract : Background: Anti-nuclear antibody (ANA) patterns in indirect immunofluorescence testing (IIF) have been valuable in the diagnosis of autoimmune diseases. A pattern of speckling with fluorescent mitotic dots is considered to represent autoantibodies against nucleolar organising regions (NORs). Anti-NOR90 antibodies target the human upstream binding factor (hUBF) which activates RNA polymerase I-activated ribosomal RNA transcription. They have been anecdotally associated with systemic sclerosis (SSc), Sjögren's Syndrome (pSS) and rheumatoid arthritis (RA). Objectives: To analyse the prevalence and clinical characteristics of patients found to be anti-NOR90 positive by immunology at The Dudley Group NHS FT (DGH) which also serves Worcestershire Acute Hospitals NHS Trust (WAH). Methods: Clinical letters and electronic patient records of anti-NOR90 positive patients identified in the DGH immunology laboratory between July 2016 and October 2017 were reviewed. Advice was sought regarding ethical approval and consent; this was deemed unnecessary for this clinical survey. Anonymized patient data was collected on Excel. Anti-NOR90 was tested for when the characteristic ANA pattern was observed and as part of an extended SSc blot (EUROLINE SSc (Nucleoli) profile (IgG) – EUROIMMUN). Results: We identified 11 anti-NOR90 positive patients among 8000 positive ANA results (estimated prevalence 0.0137%). Patient demographics, diagnoses and immunology are illustrated in table 1. Patients were in their vast majority female (10/11, 91%) and had a median age of 63 (IQR:53–74) years. The median anti-NOR90 titer was 111 (IQR:14–139) intensity units. 6/11 (54.5%) had a confirmed diagnosis of rheumatic disease. The most common clinical features were Raynaud's phenomenon (63.6%), sicca symptomatology (36.4%) and polyarthritis (36.4%). Interstitial lung disease (ILD) and oesophageal dysmotility (OD) were predominant clinical features in two cases (SSc, pSS). In general, patients lacked skin involvement (scleroderma, telangiectasias, calcinosis). Conclusions: Literature regarding anti-NOR90 auto-antibodies has been scarce and in the age of automated IIF ANA testing, it is plausible that their specific nucleolar pattern is frequently missed. In our survey, they were observed in the context of several rheumatic diseases and linked to Raynaud's, sicca symptoms and polyarthritis. Studies in larger relevant patient cohorts are needed to further clarify their clinical value. Disclosure of Interest: None declared